Role of Dof Transcription Factors under Abiotic Stresses - Amjid Khan; Fouzia Bibi; Sohail Ahmad Jan; Zabta Khan Shinwari (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
For the survival of the rapidly growing global population, plant species must exhibit tolerance towards climate change. Plants possess mechanisms to respond to stress by changing their biological processes and stimulating stress-responsive genes. The Dof (TFs) family, which binds to DNA with a single finger, reflects a plant-specific group of TFs that play an important part in regulating plants that are facing different types of abiotic stresses which may influence their growth and development. Discovery of this family has made a significant impact on the field of plant sciences. However, the characterization of Dof transcription factors in crop plants is currently limited reported. Several Dof transcription factors (TFs) of plants have been shown in nature. The transcription factors TaDofs, StDof, MnDofs, JrDof3TF, Va/VvDofs, GhDof1, OsDof1, SmeDof, ZmDof, CsDof, DcDof, CaDofs, ThDof, BraDof, and AcDof are important for abiotic stressors such heat, cold, salt, drought, and heavy metals. In addition, Dof transcription factors play a role in the regulation of factors related to yield and quality. Nevertheless, some outstanding issues remain. The review article provides a summary of the role of various stress-responsive Dof transcription factors in response to abiotic stresses. Additionally, this study investigates the limitations and possible opportunities associated with Dof transcription factors in the development of crops that are capable of withstanding climate change. Therefore, it is recommended to conduct comprehensive research on Dof transcription factors (TFs) across many different transcription factors fields to find their potential novel functionality, which will be beneficial to our retention of the delicate biological processes in plants.